1- Socialisme et Liberté - Senghor, Léopofd Sédar (Africa Development, 1977)
Elsewhere in this volume the view that socialism implies a fr society of free individuals has been expressed. What does this mean 1 Inthis article the author discusses this very issue. Defining socialism as being a method of action in the servicE of the whole man, the author notes that socialism appears in all it rigour as a perpetual spirit of research, proposing a design of societ:v based on justice in the solidarity of men, and hence on liberty, because based on the science of man. It is in this perspective that socialism as a study and then a scientific theory of society is based on genera truths, valid for all times and for all countries, but also on particula truths, since the former are rooted in the latter and the ultimate goa of socialism is the liberation and self-realization of man, placed in a particular socio-cultural context. In these truths, dialectics as a scien tific method of analysis but also of synthesis, and planning as a method symbiosis, i.e. of rational organization of production or, more generally, of the generic activity of man, occupy a foremost place The particular truths contained in scientific socialism concern the relations between the base and the superstructure. the theorv of uniform development, but above all the theory of the « class struggle ». These truths are not exportable from one specific socio-cultural space, with its specific economic realities and its original values of civilization, to another, different, universe: they apply to men « of flesh and blood ,», determined by their history and their geography, their ethnie group and their culture. Thus the study of the conditions of specific workers situated in the capitalist system ena'bled Marx to distinguish three fundamental forms of alienation: alienation from the product of labour, alienation from the act of labour, and alienation from generic life. The concept remained a tool of theoretical analysis, but imbued with a specific soc.ial and economic significance ; it became a scientific concept, but with forward-looking a,pproach, an efficient tool which would enable the workers to ,become clearly aware of their exploited condition; hence it became an instrument of political liberation, and, more thain that, of cultural flowering. For the point is to inform the workers in the capitalist system based on wage labour, how, starting from a situation of alienation in which they are treated as commodities through the sale of their labour power, they can organize in order to obtain more fitting conditions of existence in which man will be his own creator. It is on the basis of this organization that producers, in association, win remlate their exchanges on the one hand among themselves and on the other hand with nature, which they will have adapted to serve their needs. Beyond that, there will begjn the deve lopment of human aptitudes and possibilities as an end in itself, especiany in the field of art. Therein lies the whole humanist outlook of socialism: a society of free men, sociany disalienated and culturany flourishing. In a word, socialism is essentially the self-creation of man. The problems of liberty can only be posed correctly from the view point of the liberation of the most numerous and most restricted class, i.e. the working class. That is why the ultimate purpose of socia lism, the establishment of a society based on the solidarity of men in justice, is also that of freedom and democracy. These essential attributes of man can therefore only floutjsh in the context of a society in which the social relations based on the exploitation of man by man are not only abolished, but also replaced by relations based on equality and solidarity, and hence on justice. Only under these conditions can man, who is a set of needs, attain self-realization as a being in an bis cultural plenitUde. He will then become conscious of himself and of his creative possibilities : he will have fully regained his freedom. Socialism, without liberty as a major objective, can be nothing but totalitarianism, because it would be the negation of man. One cannot claim to build a design of society in a socialist perspective if one denies the fundamental human attribute, i.e. freedom : freedom in action, in work, in creation, or, in other words, the possibility for man to develop an his individual faculties in a collective society which also has freedom of self-determination.